Pentingnya Kepemimpinan dan Kerjasama Tim Dalam Implemeentasi Manajemen Mutu Terpadu - Rahmawati, Salma Nur Azizah; Supriyanto, Achmad (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2020)
The relationship between leadership and teamwork with the implementation of total quality management is a very significant relationship. Leadership an important role in the success of an organization. Leadership is based on the nature of someone who is able to change others to achieve a goal. In addition, teamwork also influences the organization's success. The purpose of this study was to determine the effect of leadership and teamwork in improving the quality of education in Indonesia. This research uses literature study methods from various journals. The results of the research are facts about the importance of leadership and teamwork in implementing total quality management.